Understanding Islamic Education Management in Digital Era: What Experts Say - Silvia Ekasari; Sardjana Orba Manullang; Abdul Wahab Syakhrani; Husna Amin (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
Since technology changed the world, all business activities have changed completely, especially in developed countries significantly. As a result, state leaders adopted a policy that had never happened, namely the application of technology in all fields so that almost all activities in the world used technology to continue activities even though they were not fully ready. Likewise, by incorporating technology into education, which is now increasingly digital, the education industry can continue to be sustainable, more affordable, and achieve maximum goals. In particular, this study wants to understand the application of technology in Islamic education governance. For this reason, our data search efforts are carried out with electronic assistance, Google Scholar, in other applications. Our analysis then involves coding the system, evaluating, and interpreting the data in depth to produce valid and reliable findings. We conducted this study in a qualitative data review design on publications published from 2010 to 2021 to find the most recent data. Based on the discussion of the findings data, it can be concluded that these findings have answered several questions, including that the management of Islamic education institutions appreciates and appreciates the use of digital technology or websites in graduate preparation programs that have the same knowledge and upskills balance between the interests of the world and the preparation for the hereafter.